Delays in receiving Alteplase and related factors in patients with stroke referred to Shahid Beheshti Hospital in Kashan-Iran in 2020-2021 - Zahra Sadat Sirousinejad; Mansour Dianati; Mahdi Kheiran; Zahra Sooki (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The benefits of using Alteplase are time-dependent. This study aimed to evaluate delays between the onset of symptoms and the administration of Alteplase and related factors in patients with acute ischemic stroke (AIS). MATERIALS AND METHODS: In this cross-sectional study, 60 AIS patients receiving Alteplase were selected by census sampling from July 2020 to July 2021 from the eligible patients referred to Shahid Beheshti Hospital in Kashan, Iran. The data collection tool was a researcher-made questionnaire containing demographic information, time periods from the onset of symptoms to the injection of Alteplase, and associated factors. The required information was collected from the patients, their relatives, their health records, and Kashan Emergency Medical Service (EMS) information system. Data were analyzed in SPSS-16. RESULTS: Eighty-five percent of the 60 patients participating in the study were transferred to the hospital by EMS ambulances. The mean time intervals between different phases were as follows: Onset-To-Door (OTD) time 81.35 ± 33.76 minutes; Door-To-CT (DTC) scan time 16.12 ± 17.46 minutes; Door-To-Needle (DNT) time 51.30 ± 26.14 minutes; and the overall Onset-To-Needle (ONT) time 133.75 ± 39.17 minutes. Also, the mean ONT in people transferred by EMS was about 129 minutes, and the longest prehospital delay in these patients was related to the time between the arrival of the EMS ambulance to the hospital. Marital status and geographical location where the stroke had occurred showed a significant relationship with prehospital delay and pre-hospital notification (PHN) by EMS But there was no relationship between underlying diseases or economic status and prehospital delays; also, the patient's diastolic blood pressure at the time of receiving Alteplase showed a significant relationship with in-hospital delay. CONCLUSION: The findings of the study showed that the majority of people trust and use EMS ambulances to transfer to the hospital and the time spent in different stages, from the onset of symptoms to the injection of the thrombolytic drug, was in an acceptable range in the patients.